A Model of Volleyball Smash Skills Exercise Model for High School Beginners Athletes - Islam, Rio Wakhid (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2019)
The purpose of this study is to apply and develop a form of smash training for volleyball, obtain empirical data about the effectiveness and efficiency of the results of the development of volleyball smash exercises , Improve the results of volleyball smash accuracy training results Provide variations in the form of training so athletes do not get bored. Research on the development of volleyball attack exercises uses a qualitative approach and uses the Research & Development (R&D) research method which consists of ten steps, among others. The subjects of this study were beginner volleyball athletes of high school age in the city of Jayapura. Before the data were analyzed, a normality test was carried out on the results of the pretest and posttest smash volleyball using the Lilliefors test at a significant level a = 0.05. The volleyball smash results between pretest and posttest obtained tOpretest = 0.7982 and tOposttest = 0.843951699 is greater than tt = 0.114, then the null hypothesis is rejected and tO = 0,000 is smaller than tt = 0.005 which means that there is a significant difference between pretest and posttest. Based on the results shows that the product of this exercise model is feasible to use, in small or large group trials. The novelty in this study is that the training model developed is a target-based smash training model.               Based on the results of the development it can be concluded that: (1) With the volleyball smash model for beginner high school age athletes, athletes can learn effectively and efficiently. (2) With the model that researchers have developed, athletes are more motivated and active in participating in smash exercises . Research Results shows that the product of this exercise model is feasible to use, in small or large group trials. The novelty in this study is that the training model developed is a target-based smash training model .   Keywords: Exercise Model, Smash Bolavoli